Intramuscular Myxoma in the Thenar Eminence: Literature Review and a Rare Case Report - Salma I. Jarrar, MD; Salim N. Al Lahham, MD (Plastic and Reconstructive Surgery, Global Open)
Summary:. Intramuscular myxoma (IM) is a rare benign soft-tissue neoplasm that most commonly involves the thigh muscles. It presents as a painless, solitary, slow-growing mass. The definitive diagnosis of IM can only be made by histopathological examination of the lesion. IM of the hand is extremely rare, with less than 5 cases being reported in the thenar eminence. Here we present a 54-year-old woman with a 10-year history of IM in the thenar eminence muscles.